Practices' systematization of stoma site marking in patients undergoing unplanned surgery: an improvement quality project - Igor Soares-Pinto; Marta Ferreira Sá; Rui Cruz; Isabel de Jesus Oliveira (Instituto Politécnico de Viseu, 2023)
Introduction:  In unplanned surgery, stoma site marking is unusual, increasing the risk of complications. Data on stoma site marking in a hospital in the northern region of Portugal and guidance in emergency situations are unavailable. Objective: To increase bowel elimination stoma site marking for patients undergoing unplanned surgery. Methods: A protocol for a best practice implementation project based on the Plan-Do-Check-Act cycle and consists of 4 phases: identification of the problem; analysis of the causes and the definition of the specific objectives; planning and implementing the intervention,  checking the results, proposing corrective measures, standardizing procedures, and training the team. Data will be gathered using questionnaires for nurses, analysis of existing information systems, and the implementation of an audit grid. Results: The first two phases allowed the identification of the main shortcomings and draft of a multimodal intervention that will comprise educational strategies, implementation of a decision-making algorithm, and audit. A decrease in skin complications is expected. Increased confidence, independence in stoma self-care, and awareness of stoma living are also anticipated. Implementing this project may lead to a reduction in healthcare costs and an overall improvement in the quality of life of the person with a stoma. Conclusion: Evidence suggests that stoma site marking is paramount to improve patient's health outcomes. Results from this project may offer new strategies to cope with management shortcomings in health systems.